Criminology and Forensic Studies: An Interdisciplinary Nexus. - Thakur, Monika; Mohan Gupta, Chander (Generate Digital Publishing, 2025)
Objective: This study aims to explore the fundamental concepts, historical development, and points of convergence between criminology and forensic science, highlighting how their integration enhances understanding, investigation, and resolution of criminal activity. Research Design & Methods: A conceptual research approach is employed, involving comprehensive literature review and theoretical analysis to examine the evolution, interdisciplinary interactions, and emerging synergies between criminology and forensic studies. Findings: The study reveals that criminology and forensic science, while distinct, increasingly intersect through multidisciplinary applications, fostering evidence-based practices and more effective approaches to crime analysis, prevention, and resolution. Implications & Recommendations: The findings suggest the need for integrated academic curricula and practical frameworks that combine sociological insight with scientific rigor, encouraging collaboration between social scientists and forensic practitioners for enhanced criminal justice outcomes. Contribution & Value Added: This research contributes by providing a holistic understanding of crime through the integration of criminological theory and forensic science, offering valuable guidance for policy makers, educators, and practitioners seeking to develop evidence-based, multidisciplinary strategies in crime prevention and justice delivery.